2021
DOI: 10.21106/ijma.409
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Intrapartum Stillbirths among Women Delivering at Mulago Hospital, Kampala, Uganda

Abstract: Background: Over the last decade, Uganda has registered a significant improvement in the utilization of maternity care services. Unfortunately, this has not resulted in a significant and commensurate improvement in the maternal and child health (MCH) indicators. More than half of all the stillbirths (54 per 1,000 deliveries) occur in the peripartum period. Understanding the predictors of preventable stillbirths (SB) will inform the formulation of strategies to reduce this preventable loss of newborns in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…In multivariate analysis no statistical link was found ( p = 0.236). This result corroborates that of Sandjong et al in Cameroon ( 8 ). where the risk of stillbirth was high when the patient is referred by another health facility; [OR = 4.81, 95% CI (2.39–9.91); p < 0.001].…”
Section: Discussionsupporting
confidence: 93%
“…In multivariate analysis no statistical link was found ( p = 0.236). This result corroborates that of Sandjong et al in Cameroon ( 8 ). where the risk of stillbirth was high when the patient is referred by another health facility; [OR = 4.81, 95% CI (2.39–9.91); p < 0.001].…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that, compared to female sex, male sex was more likely to experience stillbirth. This result is consistent with various stillbirth investigations in Nigeria (13), Ghana (40), and Cameroon (18). This result con icts with other studies conducted in Nigeria (24), and Cameroon (18).…”
Section: Discussionsupporting
confidence: 93%
“…In relation to the response rate, the primary articles incorporated in the meta-analysis ranged from 92.7-100%, and essentially all the studies had a good response rate. Forty (40) of the forty-one (41) studies were published (1)-( 30), (32)(33)(34)(35)(36)(37)(38)(39)(40)(41), while one (1) was unpublished (a PhD thesis) in reputable journals (31). Lastly, the primary studies included in the present systematic review and meta-analysis had a quality score of 8-10 out of 10 points.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This is partly due to the hospital being a referral site and most of the deaths are due to conditions that are preventable, such as excessive bleeding, hypertensive disorders of pregnancy (pre-eclampsia/eclampsia), sepsis (bacterial infection) from obstructed labour and abortion-related complications. Serious conditions are compounded by delay in seeking care, delays in getting transport and delays waiting at health facilities (Kiondo et al, 2021;Nakimuli et al, 2016). Most of the women who die, die young, with a mean age of about 26 years, and of these 10 to 15% are adolescents/young adults (< 20 years) (Ministry of Health, 2018).…”
Section: The Imelda Namagembe Study "Implementation Of Maternal Death...mentioning
confidence: 99%